The influence of digital financial literacy and financial technology on managerial performance in Vapestores - Erlangga Defry Sutardjo; Jullie J. Sondakh; Djeini Maradesa (Yayasan Widyantara Nawasena Raharja, 2026)
This study investigates whether digital financial literacy and financial technology improve managerial performance in vapestore businesses. The rapid expansion of the vapestore industry has increased competition and required managers to enhance financial management capabilities and adopt digital financial tools. However, many vapestore managers still face limitations in digital financial literacy and financial technology utilization, which may hinder managerial effectiveness. This study uses a quantitative approach with data collected from 40 vapestore managers in Manado, Tomohon, Mandolang, and Airmadidi. Data were analyzed using multiple linear regression with SPSS 26. The findings reveal that digital financial literacy has a positive and significant effect on managerial performance, as indicated by a regression coefficient of 0.591 and a significance value of 0.000. Financial technology also has a positive and significant effect, with a regression coefficient of 0.492 and a significance value of 0.000. Furthermore, the adjusted coefficient of determination shows that 88.4% of managerial performance is explained by digital financial literacy and financial technology, while 11.6% is explained by other factors outside the model. These results indicate that strengthening digital financial literacy and optimizing financial technology utilization are important in improving managerial performance in vapestore businesses.